(untitled) (International Journal of Culture and Art Studies, 2021)
This research discusses the analysis of the concept of speech among some ethnic groups in West Africa. In fact, in West Africa, the art of speaking is brought to a high degree of perfection.Â According to those ethnic groups discussed in this paper, the speech possesses a mystical, talismanic power, which means that it has the power to protect and change the course of events. The Nommo’s conception of life can illustrate this idea in that they consider that life itself lies on speech without which it can never exist. Also, they consider that there is a close relationship between speech and the speaker. However, speaking is more than just lining up words to be understood by the interlocutor, the audience. It is considered an art that must respect certain rules relating to the place, the time and the person speaking. In this sense, the researcher, in this paper, tries to analyze the concept of speech in these ethnic groups of West Africa. The research uses secondary data as the method, otherwise called â€œliterature reviewâ€. In other words, the researcher proceeded to collect the data related to the paper’s topic by downloading them and then proceeded to the analyzes and comments.